Analisis Strategi Guru Mengatasi Kesulitan Siswa dalam Menyelesaikan Soal Perkalian di Sekolah Dasar - Tri Lestari, Reni; Adrias, Adrias; Putri Zulkarnaini, Aissy (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to analyze the difficulties faced by elementary school students in solving multiplication problems and the strategies implemented by teachers to address them. The background of this research lies in the importance of understanding multiplication as a foundational concept for mastering more advanced mathematical operations. This research employed a descriptive qualitative approach, using interviews as the primary data collection technique. The findings revealed that students struggle with understanding multiplication as repeated addition, applying problem-solving strategies, and maintaining accuracy due to over-reliance on rote memorization without conceptual understanding. To overcome these issues, teachers implemented various strategies such as the use of interactive learning media, concrete manipulatives, game-based learning, gradual practice, and individualized guidance in collaboration with parents. These strategies have proven effective in improving students’ conceptual understanding, accuracy, and confidence in solving multiplication problems.